2010
DOI: 10.1111/j.1365-3040.2010.02179.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in the Populus balsamifera drought transcriptome

Abstract: Drought is a major limitation to the growth and productivity of trees in the ecologically and economically important genus Populus. The ability of Populus trees to contend with drought is a function of genome responsiveness to this environmental insult, involving reconfiguration of the transcriptome to appropriately remodel growth, development and metabolism. Here we test hypotheses aimed at examining the extent of intraspecific variation in the drought transcriptome using six different Populus balsamifera L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 53 publications
(79 reference statements)
2
39
2
1
Order By: Relevance
“…RNA analysis, transcript abundance detection with Affymetrix GeneChip Poplar Genome Array, qRT-PCR, and microarray analysis were performed largely as previously described (14,15). Details are provided in SI Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
“…RNA analysis, transcript abundance detection with Affymetrix GeneChip Poplar Genome Array, qRT-PCR, and microarray analysis were performed largely as previously described (14,15). Details are provided in SI Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype specificity of transcriptomic, proteomic, or metabolomic responses has been highlighted by many studies. Comparing six genotypes of Populus balsamifera, Hamanishi et al (2010) showed that the growth response to drought was correlated with genetic responsiveness. In P. deltoides × nigra, the phenotypic response to moderate drought was found to be very similar for a stress-tolerant and a stress-sensitive genotype, and the differences in transcriptional responses were therefore attributed to intrinsic divergences in genome functioning (Cohen et al 2010).…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…Modulation of species-specific responses to drought by local populations and genotypes has been intensively studied in a number of trees including e.g. Betula (Aspelmeier & Leuschner, 2004, 2006, Quercus (Kremer, 2010), Populus (Hamanishi et al, 2010) or Pinus (Aranda et al, 2010), indicating that functional responses to water deficit are at least in part under genetic control. The response to drought is a complex process, and combined genomic and phenotypic analyses can enhance our understanding of this fundamental response as exemplified by two studies in poplar.…”
Section: Adaptation and Natural Variation Of Droughtmentioning
confidence: 99%
“…In addition, genotypes that differed strongly in leaf abscission behaviour under drought were found to induce the expression of different sets of genes, suggesting adaptation at the level of gene expression (Street et al, 2006). Intraspecific variation of drought responses in balsam poplar (Populus balsamifera) was investigated by comparing phenotypic traits with gene expression profiles (Hamanishi et al, 2010). Genotypes that were able to sustain growth under drought conditions also exhibited a higher magnitude of stress-induced changes in gene expression.…”
Section: Adaptation and Natural Variation Of Droughtmentioning
confidence: 99%